ROLE OF NEUROPEPTIDES AND OTHER NEUROMODULATORS IN TENDINOPATHY PATHOGENESIS. Issue 9 (10th May 2013) - Danielson, P
Abstract : The biochemical micromilieu of human tendons has gained increasing interest during the last decade. Partly prompted by microdialysis studies of both Achilles and patellar tendons, demonstrating an unexpectedly augmented level of the neurotransmitter glutamate in tendinopathy, 1 2 Khan et al first suggested a new paradigm concerning tendinopathy pathogenesis, 3 in part contradicting already established theories. They suggested that the underlying mechanism of tendinopathy might be biochemical rather than structural. Since then, much contemporary research has been directed towards trying to answer the question of the possible role of biochemical agents in the development of tendon pain and degenerative-like tissue changes, that is, tendinosis. At the cellular level, tendon cells in tendinosis tissue have indeed been shown to produce an array of signal substances that were once thought to be restricted to neurones. Although the functional importance of such biochemical agents in tendinopathy remains to be determined, evidence of a dramatic change in local cell signalling within chronically painful tendons exists. Studies have demonstrated that there is a local, non-neuronal production in the tenocytes of traditionally neuronal mediators, like neuropeptides. These findings include acetylcholine, 4 5 – 6 catecholamines, 7 8 – 9 glutamate, 10 and the neuropeptide substance P (SP).11 Furthermore, the receptors for several of these signal substances have been found on nerve fascicles and in blood vessel walls (as well as on the tenocytes themselves) of the tendon tissue. These results suggest that locally produced neuromodulators may influence pain signalling, angiogenesis and vascular regulation, as well as cellular and tissue changes, like cell proliferation and/or apoptosis and matrix remodelling, in tendinopathy.12 Results of novel experimental studies on both in vivo13 and in vitro14 models of tendinopathy have revealed the neuropeptide SP as a key player in cellular regulation of tendinosis. Endogenous production of SP by tendon tissue/cells is significantly increased after mechanical load14 15 and SP furthermore contributes to development of tendinosis tissue characteristics; promoting hypercellularity and angiogenesis.14 16 Very recent unpublished data, presented at this conference, further underline the role of SP, but also acetylcholine, as important mediators in tendinosis. Not least interesting in this respect is the fact that SP inhibits tenocyte apoptosis and consequently prevents self-regulatory mechanisms that should limit the amount of collagen producing cells and prohibit excessive collagen accumulation in tendinosis. All these studies strengthen the biochemical hypothesis, 3 suggesting that the underlying pathology of tendinopathy is primarily of biochemical origin rather than mechanical (albeit perhaps indirectly through mechanotransduction). We believe that such a biochemical paradigm of tendinopathy can complement, rather than replace, existing theories. We furthermore believe that this hypothesis fits a theoretical model, put forth by Cook and Purdam, in which tendon pathology is proposed to exist on a continuum that at various points involves several tendon tissue abnormalities.17 This key note lecture aims at giving a brief orientation of the evidence to date in favour of the 'biochemical model of tendinopathy'.